2006
DOI: 10.1142/s0218001406004776
|View full text |Cite
|
Sign up to set email alerts
|

User Independent Gesture Interaction for Small Handheld Devices

Abstract: Accelerometer-based gesture recognition facilitates a complementary interaction modality for controlling mobile devices and home appliances. Using gestures for the task of home appliance control requires use of the same device and gestures by different persons, i.e. user independent gesture recognition. The practical application in small embedded low-resource devices also requires high computational performance. The user independent gesture recognition accuracy was evaluated with a set of eight gestures and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…As summarized in the section on related works before, Kallio et al [12] reported an average processing delay of 8.3 ms for a discrete 5-state HMM. However, the authors did not report on their implementation details.…”
Section: B Processing Performance Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As summarized in the section on related works before, Kallio et al [12] reported an average processing delay of 8.3 ms for a discrete 5-state HMM. However, the authors did not report on their implementation details.…”
Section: B Processing Performance Resultsmentioning
confidence: 97%
“…Among the few HMM-based recognition implementations that have been analyzed for gesture recognition in mobile systems, Kallio et al [12] reported an average processing delay of 8.3 ms for a discrete 5-state HMM. However, their investigation only addressed HMM classification and did not consider a complete procedure for continuous recognition, covering spotting and classification.…”
Section: Related Workmentioning
confidence: 99%
“…Examples of motion and gesture recognition include immersive gaming [8], [9], and many forms of computer interaction, e.g. [10], [11], [12]. Sign language recognition is a closely related topic and considered in several works, e.g.…”
Section: B Related Workmentioning
confidence: 99%
“…Kallio et al [9] presented an application using acceleration sensors embedded in a remote control to manage home appliances. Their work was focused on confirming the feasibility for classifying different gestures using hidden Markov models (HMMs).…”
Section: Gesture-operated Mobile Devicesmentioning
confidence: 99%